HEALTHY LIVING ENVIRONMENT IN KUALA LUMPUR PUBLIC PARKS - Baharuddin, Zainul Mukrim (Journal of Architecture, Planning and Construction Management, 2018)
Providing a healthy living environment is one of the key issues for planners and designers. Various urban design and planning approaches have been debated worldwide to provide healthy living. Rapid urbanization and its impact on social, environmental and health quality. These issues are more acute in developing countries than in developed countries. Urban public parks offer many opportunities for urban dwellers to achieve a healthy living environment. Thus, this paper investigates people’s interaction with open space and the benefits of urban parks in Kuala Lumpur. Opinions of visitors from the nine urban parks in Kuala Lumpur were collected to address the aim of the research. Various levels of urban park such as the city parks, district and neighborhood parks were investigated. The parks represent all five districts in Kuala Lumpur. Altogether, 47 respondents were interviewed at seven parks. Information collected through the interview survey was analyzed using qualitative analysis techniques. The research indicate that people are involved with active and passive activities in urban public parks. The result showed that 65.42% of respondents participated in active activities such as jogging and exercise. Meanwhile, 34.57% preferred passive activities such sightseeing, rest and relaxation. The results also indicated that, when people interact with nature, 39.08% agreed that social integration is the greatest benefit of their urban living environment. Secondly, 28.74% agreed on health benefit. Thirdly, 18.39% agreed that urban parks could provide environmental benefits and lastly was the benefits of parks management (11.49%). Finally, the study concluded that a healthy living environment can be promoted through frequent visits to urban parks by participating in activities and nature appreciation. Therefore, it is important to enhance the green strategies within urban planning and design strategy to improve healthy living.